Assessment of the Optimal Site of Femoral Artery Puncture and Angiographic Anatomical Study of the Common Femoral Artery - Ahn, Ho-Young (The Korean Neurosurgical Society, 2014)
OBJECTIVE: The purpose of this study was to evaluate demographic and clinical factors affecting the common femoral artery diameter and length, and anatomical relationship between the femoral head and the common femoral artery during angiography. METHODS: We retrospectively reviewed 109 femoral angiograms. We collected the clinical data of the patients and estimated the common femoral artery diameter and length. We divided the areas in the angiogram from cephalic to caudal direction (zone 0 to 5). The lowest levels of the inferior epigastric artery loop and points of the common femoral artery bifurcation were checked. RESULTS: The luminal diameter of the common femoral artery was 6.19±1.20 mm. Height, weight, body surface area, as well as common femoral artery diameter were significantly greater in men than in women (p<0.005). The length of the common femoral artery was 27.59±8.87 mm. Height, weight and body surface area showed strong positive relationships with common femoral artery diameter. All of the inferior epigastric artery loops were located above the center of the femoral head. The point of common femoral artery bifurcation was above the center of the femoral head in 4.59% of femoral angiograms. CONCLUSIONS: Males and patients with a high body surface area have a larger common femoral artery diameter. The cumulative probability of optimal targeting between the lowest margin of the inferior epigastric artery loop and the common femoral artery bifurcation is the highest in zone 3 puncture.